Analisis Kemampuan Menulis Puisi Siswa Kelas IV di SDN Paninggaran - Dadang Cunandar; Siska Isnaiyah Pebriani; Atang Sutisna (Jurnal Lensa Pendas, 2024)
Analysis of the ability to write poetry is an activity to describe students' poetry writing abilities seen from various aspects of ability. These aspects include imagination, diction, explanation, themes, and mandates. In poetry there are goals and elements in poetry. This study aims to determine the poetry writing skills of grade IV SDN Paninggaran students. This research is a qualitative research. The subjects in this study were the fourth grade homeroom teacher and the fourth grade students. The number of students in grade IV SDN Paninggaran is 35 students. This data was collected through interviews and documentation. The results of this study indicate that the ability to write poetry of fourth grade students is that most grade IV students like learning poetry and are able to write poetry but students find it difficult to put ideas into writing and determine how it is stanzas, lines, rhymes, determining pauses and intonations but from the mandate aspect tends to provide advice to the reader.